Strategi Dakwah Nahdlatul Ulama Dan Muhammadiyah Dalam Perspektif Pemanfaatan Media Massa Pada Era Globlalisasi Di Kabupaten Pacitan - Alviendra Alviendra; Chintia Maria Nur Faddillah; Andhita Risko Faristiana (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
Good media and audience support good strategy, in general. From among the many different media that can be used as an Islamic propaganda tool, mass media is currently the most effective and efficient. The two largest organizations in the Pacific region are Nahdlatul Ulama and Muhammadiyah. The success of this Islamic organization in promoting dakwah is directly related to the application of sound and reliable dakwah strategies. The current study analyzes the tactics used by the two largest organizations, Nahdlatul Ulama and Muhammadiyah, in Kabupaten Pacitan, to spread Islam through public media. The current study makes use of techniques for collecting data up to and including data analysis that are appropriate for qualitative research methodologies to uncover data-data that shed light on a problem that has already been raised, specifically the comparison of media mass media use strategies across two study objectives. After conducting research with the available data, it is possible to draw the conclusion that the most effective method of mass media use for organizations like the Muslim Brotherhood's Nahdlatul Ulama is through online media, while organizations like the Muhammadiyah are also effective when using online media. Similar and different. The collaboration between the two organizations in this regard is focused on using the media mass as it is, as well as on working together with other media mass. The opposite is also true, as evidenced by the widespread use of media by nahdatul ulama and the Muslim community. Because Nahdatul Ulama and Muhammadiyah are predominately Nahdatul Ulama in Pacitan as a whole, Nahdatul Ulama use the media more frequently than Muhammadiyah does.